Is Elite Sport (Really) Bad for You? Can We Answer the Question? - Lebrun, Florence; Collins, Dave (Frontiers in Psychology, 2017)
Elite athletes are not immune to mental health issues. Yet, quality research on mental health in elites has so far been limited. Thus, while research on mental health emphasises the prevalence and nature of disorders in the general population, its extent in elite performers remains unclear. Indeed, the prevalence of mental conditions cannot be accurately calculated in elite athletes due to a lack of diagnostic criteria and screening tools specifically adapted to this unique population. Researchers and practitioners are, therefore, confronted with biases reflecting the use of clinical norms and instruments initially developed for the general population. Furthermore, without considering the athlete persona as well as the sport culture in which elites play, there is a risk of under- or overestimating the prevalence of mental health issues in high-performance environments. Due to the unique characteristics surrounding an elite athlete’s life, we therefore suggest a change of perspective: moving from the usual normal-versus-pathological to a functional-versus-dysfunctional approach. Implications for future research and practice are discussed, most notably examining practitioners’ expertise in diagnosing and treating elite performers.